The parliament of man : the past, present, and future of the United Nations - Kennedy, Paul M., 1945- (New York : Random House, 2006)
Scholar Kennedy gives a thorough history of the United Nations that explains the institution's roots and functions while also casting an eye on the UN's effectiveness as a body and on its prospects for success in meeting coming challenges. He makes sense of the commissions and committees, and how the six main operating bodies operate and interact. Citing examples from history, he shows how the five permanent members of the Security Council on numerous occasions overcame political antagonisms to spearhead military supervision of aid in humanitarian crises, and how lack of cooperation among the great powers has hamstrung such initiatives as the control of greenhouse gas emissions and exacerbated the deleterious effects of globalization on developing nations' economies. As a body, the UN emerges here for what it is: fallible, human-based, oftentimes dependent on the whims of powerful nations or the foibles of individual senior administrators, but utterly indispensable.--From publisher description.
THE ORIGINS: The troubled advance to a New World Order, 1815-1945 -- THE EVOLUTION OF THE MANY UNs SINCE 1954: The conundrum of the Security Council -- Peacekeeping and warmaking -- Economic agendas, north and south -- The softer face of the UN's mission -- Advancing international human rights -- "We the peoples": democracy, governments and nongovernmental actors -- THE PRESENT AND FUTURE: The promise and peril of the 21st century.
Includes bibliographical references (p. [295]-311) and index.
Keywords: United Nations -- History; International relations